2008 International Conference on Computing, Communication and Networking 2008
DOI: 10.1109/icccnet.2008.4787714
|View full text |Cite
|
Sign up to set email alerts
|

Training MLP neural network to reduce false alerts in IDS

Abstract: Due to the tremendous growth of the Internet and Network based services, the severity of network based computer attacks have significantly increased. Thus, IDS play a vital role in network security. Intrusion detection system tries to detect computer attacks by examining various data records, log audits etc. Many existing IDS such as Snort are signature based system. The problem with such a system is that it cannot detect novel attacks whose signature is not available and hence generates a high rate of alerts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In conclusion, the model achieves the best performance when normal_log � 11, sequence_window � 13, num_layers � 2, and hidden_size � 64. e further comparative study showed that the proposed method has better performance than other deep learning algorithms and traditional machine learning algorithms. is paper selects MLP [41], RBM [42], SVM [43], and naive Bayes algorithms [44] for comparative analysis, uses comprehensive F1-score indicators for comparison, and uses training samples of different magnitudes. As shown in Figure 10, the algorithm proposed in this paper achieves a more accurate recognition rate than traditional machine learning algorithms and has better results than ordinary deep learning algorithms.…”
Section: Word2vecmentioning
confidence: 99%
“…In conclusion, the model achieves the best performance when normal_log � 11, sequence_window � 13, num_layers � 2, and hidden_size � 64. e further comparative study showed that the proposed method has better performance than other deep learning algorithms and traditional machine learning algorithms. is paper selects MLP [41], RBM [42], SVM [43], and naive Bayes algorithms [44] for comparative analysis, uses comprehensive F1-score indicators for comparison, and uses training samples of different magnitudes. As shown in Figure 10, the algorithm proposed in this paper achieves a more accurate recognition rate than traditional machine learning algorithms and has better results than ordinary deep learning algorithms.…”
Section: Word2vecmentioning
confidence: 99%
“…Barapatre et al [24] experimented with an input layer, a hidden layer, and an output layer in the neural network. The input node contained 41 features of the KDD Cup'99 dataset.…”
Section: A Supervised Learningmentioning
confidence: 99%
“…Prachi Barapatre et al [4] used MLP with backpropagation algorithm to classify attacks. Dataset used was KDD99 dataset.…”
Section: Related Workmentioning
confidence: 99%